Osteochondritis dissecans u dětí – ošetření pomocí artroskopické techniky fokálních návrtů - Přidal, Jaromír; Šťastný, Eduard; Trč, Tomáš; Havlas, Vojtěch (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF STUDY Osteochondritis dissecans (OCHD) is an increasingly diagnosed disease among adolescent patients. It is a condition affecting subchondral bone and the lining cartilage. If left untreated, it can cause destruction of cartilage of the affected joint leading to early development of arthrosis. Mostly affected joints are knees and ankles, but affected elbow and other joints have been described too. The purpose of our study is to present the patients diagnosed and treated surgically at our clinic with arthroscopic drilling in the period 2010-2015, and subsequently the clinical findings obtained at follow-up checks after the surgery. MATERIAL AND METHODS Between 2010 and 2015, a total of 34 patients (36 joints) underwent surgical treatment at our clinic. Their age ranged from 6 to 19 years at the time of surgery, 17 girls and 17 boys underwent the surgery. All the patients were treated with transarticular antegrade arthroscopic drilling. Each patient was diagnosed based on the clinical finding, radiographs, or MRI. The patients were followed after 6 weeks, thereafter 3, 6, and 12 months after the surgery. Each patient was evaluated based on the clinical findings (presence of swelling, range of motion, and pain according to VAS), and radiographs. RESULTS The preoperative VAS was 2.9 and dropped down to 1.5 at the first follow-up visit. None of the patients complained of pain at 1-year follow-up. 34 (out of 36) patients suffered joint swelling preoperatively, 6 weeks after the surgery only 9 patients presented with ongoing swelling, at 1-year follow-up no patient reported this problem. The X-ray findings showed regression in 35 of 36 patients one year after the surgery. One female patient underwent redo surgery because of an ongoing restriction of movement and X-ray finding persistence. DISCUSSION Majority of patients with OCHD can be treated conservatively. Physical activity modification and temporary immobilization are commonly used treatment methods of this condition. If conservative treatment is unsuccessful, arthroscopy should be considered. Stable lesions have a high chance of spontaneous healing without surgery. There is a variety of arthroscopic treatment methods. Mostly transarticular transchondral drilling is used to treat this condition. CONCLUSION Treatment of OCHD with arthroscopic drilling shows promising results in our cohort of patients. We recommend to use arthroscopic drilling in patients in stage I to III according to X-ray when 3 months of conservative treatment do not improve the clinical symptoms, swelling and restriction of movement. Antegrade drilling is the most frequently used treatment method in OCHD at our clinic, we consider this technique a simple and effective, with short surgical time needed. Key words: osteochondritis dissecans, treatment, arthroscopy, drilling.
Keywords: Magnetic Resonance Imaging; Female; artroskopie; radiografie; dítě; Radiography; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; Osteochondritis Dissecans; lidé; magnetická rezonanční tomografie; osteochondritis dissecans; Treatment Outcome; následné studie; stupeň závažnosti nemoci; Follow-Up Studies; Male; Young Adult; Arthroscopy; Child; mužské pohlaví; Severity of Illness Index; mladiství; Humans